Clinical characteristics, epidemiology, and mortality of patients receiving antifungal therapy at a university hospital of the Triângulo Mineiro, Brazil - Flávia Maria Pinto Monteiro Antonieti (Revista de Epidemiologia e Controle de Infecção, 2024)
Background and Objectives: Invasive fungal infections are associated with high morbidity and mortality in patients admitted to hospital, including those receiving appropriate therapy. The aim of this study was to evaluate the use of prophylactic and preemptive antifungal therapy; clinical and epidemiological features; and mortality of patients admitted to an infectious disease ward of a public high complexity hospital in Uberlandia, Minas Gerais, Brazil. Methods: This is a retrospective study carried out in the infectious diseases ward of a public university hospital in Brazil. Data from patients hospitalized in 2019 and 2020 who received azole antifungals (fluconazole, itraconazole, or voriconazole), echinocandin (anidulafungin), and polyene (amphotericin B) were collected from medical records. Results: During the study period, 111 patients received one or more antifungal agent. The length of hospital stays of patients (29.35 days; p=0.0252), mean number of days of antibacterial drug use (23.5 days; p=0.0164), a diagnosis of AIDS (p=0.0397), mechanical ventilation (MV) (p<0.001), and presence of a nasoenteral tube (p<0.01) were variables that were associated with death. Fungal infection was confirmed in 79 (71.2%) patients who used antifungal drugs. The most frequent fungi isolated were Candida spp. (36; 32.4%) and Cryptococcus spp. (22; 19.8%), and there was an association between infection with these fungi and mortality (p<0.05; OR: 7.61 and 5.53, respectively). Regarding antifungal therapy indication, 56 (50.4%) patients received it as empirical therapy, 33 (29.7%) as targeted therapy, and 22 (19.8%) as preemptive therapy. Conclusion: The factors that contributed to mortality of the patients were longer hospital stays, AIDS, antibacterial medication use, mechanical ventilation, and presence of a nasoenteral tube. The type of antifungal therapy used did not influence the mortality in these patients.